Judge Allows Players to Make Case for Rejecting $30M Settlement in CHL Minimum-Wage Lawsuit - Westhead, Rick (TSN, 2023)
A judge will allow a lawyer for two former Quebec Major Junior Hockey League players to file evidence and make verbal arguments about why a $30 million settlement in three class-action lawsuits filed by current and former Canadian Hockey League players should be rejected.
Section: chl

Labour Day: Union Members Boost the Benefits of Organized Labour, But Almost 40% Say Membership Costs Exceed Gains - Korzinski, David (Angus Reid Institute, 2023)
...A new study from the non-profit Angus Reid Institute dives deep into perceptions of labour unions, finding a nation with competing views about the value and cost of organized work in Canada, among union members and non-members alike. Overall, Canadians largely feel that unions have had a positive impact for those they represent. Three-in-five say this, approximately three-times as many as say the impact has been a net negative. The cost-benefit calculation is more divided when considering the impact of unions on the country’s economy as a whole. Two-in-five say this impact is a positive one while three-in-ten say it has been negative. Workers themselves have their own experiences. For most, union membership has been a plus. Three-in-five members of both public (62%) and private (63%) sector unions say they’re satisfied with the representation they receive. Half as many say they’re dissatisfied, suggesting there is plenty of room for improvement. Progress may come from more than one area. Overall, among those who have gone to a union representative for assistance, three-in-ten (30%) say they did not feel supported. Women are slightly more likely to say they did not feel supported (36%) than men (30%). Further, when they think about the costs of membership and the benefits they receive, two-in-five union members (39%) say they do not receive adequate benefit for what they pay. Asked which of the main federal political parties they think is currently best suited to improve their own situation, public sector union members overwhelmingly say the NDP, traditionally associated with organized labour, is the best option (49% say this, a 31-point advantage over the next option chosen). That said, those in private sector unions are less certain. One-third say the Conservative Party would be best (32%), one-third choose the NDP (32%) and 26 per cent choose the governing Liberal Party. –Website summary

Work Stoppages in Canada, by Jurisdiction and Industry: Based on the North American Industry Classification System (NAICS) - Statistics Canada (2023)
Work stoppages, including number of work stoppages, maximum number of employees involved, average duration, and number of person-days not worked due to work stoppages by jurisdiction, industry, and sector, annually, from 1946 to 2020.
https://doi.org/10.25318/1410035201-eng